AN IMMORTAL TREASURE OF OUR NATIONAL CULTURE - Sayyora Tuychieva (American Journals Publishing, 2022)
This article provides information about the poetry that has been living among the people and its unique type - the epic school, and its place in the education of young people.
Keywords: Heritage, folklore, narrator (of folk tales)